2003
DOI: 10.1007/s00595-003-2536-0
|View full text |Cite
|
Sign up to set email alerts
|

Left Renal Vein Anomaly Associated with Abdominal Aortic Aneurysm Surgery: Report of a Case

Abstract: Retroaortic left renal vein occurs infrequently and poses potential hazards to the surgeon during abdominal aortic surgery. We herein report the case of a 77-year-old man with a retroaortic left renal vein who underwent an abdominal aortic aneurysm (AAA) repair. The retroaortic left renal vein was diagnosed preoperatively by contrast-enhanced computed tomography (CT). The patient underwent a successful abdominal aortic replacement with an uneventful postoperative course without any renal complications. The CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
(12 reference statements)
0
11
1
Order By: Relevance
“…Multiple renal veins are common on the right side (up to 15%), and anomalies of the left side comprise the retroaortic left renal vein and the circumaortic left renal vein with an incidence of 1.2-3.3 and 1.5-8.7%, respectively (Kudo et al 2003). The circumaortic left renal collar can be divided into three different morphological types (Natsis et al 2008), and this indicates the complexity of the underlying embryological development, but also the role the anastomoses play on the different morphological patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple renal veins are common on the right side (up to 15%), and anomalies of the left side comprise the retroaortic left renal vein and the circumaortic left renal vein with an incidence of 1.2-3.3 and 1.5-8.7%, respectively (Kudo et al 2003). The circumaortic left renal collar can be divided into three different morphological types (Natsis et al 2008), and this indicates the complexity of the underlying embryological development, but also the role the anastomoses play on the different morphological patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the course, number, and arrangement of the renal veins are less common from the renal arterial variations. Renal venous variations and multiple veins are seen more often on the right side than on the left side [2][3][4].…”
Section: Resultsmentioning
confidence: 96%
“…The risk of accidentally damaging a RLRV is higher for the surgeons who routinely dissect the aorta circumferentially to apply the proximal crossclamp. Careful preoperative evaluations are important for establishing the presence of an associated venous anomaly to ensure the success of abdominal aortic surgery (Satyapal et al, 1999;Karkos et al, 2001;Kudo et al, 2003). In conclusion, detailed knowledge of the presence of potential variations in renal arterial and venous anatomy is important for retroperitoneal surgery.…”
mentioning
confidence: 98%
“…We have found only one report of a bilateral accessory renal artery with RLRV. Kudo et al (2003) presented a case report of abdominal aortic aneurysm In recent years, extensive research has been reported showing certain surgical and medical aspects of accessory renal arteries. Transplanting a kidney with accessory renal arteries has several theoretical disadvantages (increased incidence of acute tubular necrosis and rejection episodes, decreased graft function, and prolonged hospitalization) (Cicekcibasi et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation